Conflict Management Diversity Among Faculty in a Private Medical University of Pakistan - Mirza, Tayyeba Iftikhar; Shukr, Irfan (Pakistan Armed Forces Medical Journal, 2026)
Objective: To evaluate the different conflict management styles among health educators at a private medical university in PakistanStudy Design: Cross-sectionalPlace and Duration of Study: Foundation University School of Health Sciences, Islamabad Pakistan from May to Jul 2024.Methodology: Faculty from MBBS, BDS, Physical Therapy, and Nursing programs participated. Data was collected using a validated self-reported questionnaire, including demographic details and the Rahim Organizational Conflict Inventory-II. Descriptive statistics were calculated, and Chi-square tests were used for associations between categorical variables. The Shapiro-Wilk test assessed the normality of experience, and the Kruskal-Wallis test was applied due to non-normal distribution (p